Second receiver selection algorithm for fairness in full duplex communiations - Lee, Won Jae; Kim, Jin Ki; Kim, Kyeong Rok; Kim, Jae Hyun (Proceedings - 2019 IEEE VTS Asia Pacific Wireless Communications Symposium, APWCS 2019, 2019)
The full-duplex (FD) wireless system can get double throughput compared to half-duplex (HD) wireless system. The FD communication can transmit and receive data at the same time. Due to that reason, the FD wireless system is affected with interference more than the HD wireless system. Therefore, the new FD MAC protocol is required that suitable for the FD wireless environment. The conventional FD MAC protocols have focussed on improving throughput and do not adequately consider performance fairness. In this paper, we propose the algorithm that selects secondary receiver (SR) considering the fairness. To evaluate performance of the proposed algorithm, we compared throughtput and fairness of the proposed algorithm with those of conventional one through computer simlation. The simulation results show that the proposed algorithm improves the fairness without throughput decrease as compared with the conventional FD MAC protocols.
Keywords: Full-duplex; Half-duplex; MAC protocol; Medium access control protocols; Receiver selections; Wireless environment; Wireless systems; Full duplex; Medium access control (MAC) protocol; Wireless lan (WLAN)